Do mirrors facilitate acquisition of motor imitation in children diagnosed with autism?. Issue 1 (12th February 2015) - Miller, Scott A.; Rodriguez, Nicole M.; Rourke, Ami J.
<x xml:space="preserve">Abstract</x> We evaluated the efficacy of a procedure that incorporated a mirror to teach gross motor imitation with a 2‐year‐old boy who had been diagnosed with autistic disorder. Responses taught with a mirror were acquired more quickly than responses taught without the mirror and were maintained after the mirror was removed. These data indicate that a mirror can facilitate acquisition of motor imitation.